Unraveling Dual Anomalies: A Case Of Acrania With Gastroschisis - Gokuldas, Mohini; Patvekar, Meenal; Suryarao, Prashant; Jagtap, Akshay; Jaiswal, Parul (Journal of Neonatal Surgery, 2025)
Acrania and gastroschisis are rare congenital anomalies that are typically incompatible with life. Acrania is a severe neural tube defect characterized by the absence of the cranial vault, often progressing to anencephaly. Gastroschisis is a congenital anterior abdominal wall defect with herniation of bowel loops, usually isolated but occasionally found in association with other anomalies. The coexistence of acrania with gastroschisis is exceptionally rare, with very few cases reported in the literature. We report the case of a 28-year-old gravida 2, para 1 woman who presented at 16 weeks of gestation with abdominal pain. She had a previous cesarean section and a history of severe oligohydramnios in her first pregnancy. The current pregnancy was un booked, and she had not taken folic acid supplementation. Antenatal ultrasonography revealed a fetus with acrania and gastroschisis. Clinical examination confirmed a 16-week-sized uterus with a closed cervix. In view of the poor prognosis, a second-trimester medical termination of pregnancy was performed. The abortus was a male fetus weighing 88 grams, with external features confirming the ultrasound findings—absence of the cranial vault and evisceration of intestines through the anterior abdominal wall. This case emphasizes the importance of early antenatal care, prenatal screening, and periconceptional folic acid supplementation in the prevention and early diagnosis of major congenital anomalies. Increased awareness and timely interventions are essential to reduce the incidence and associated morbidity of neural tube defects and abdominal wall anomalies in low-resource settings.